Improved expression of catechol 1,2-dioxygenase gene from Burkholderia cepacia in Escherichia coli - Dang, Van Thanh; Hoang, Anh Thi; Tran, Gia Cat Tuong; Pham, Thi Huyen Tran; Ha Thanh, Le Thi; Nguyen, Hoang Loc (Hue University Journal of Science: Natural Science, 2020)
Catechol 1,2-dioxygenase (CAT1) is a key enzyme for the ortho-cleavage pathway involved in the degradation of dibenzofuran, a dioxin derivative, which is a highly toxic environmental pollutant. The present study aims to investigate appropriate culture conditions for enhancing the expression of the cat1 gene encoding CAT1 enzyme from Burkholderia cepacia DF4 in Escherichia coli M15. The optimized culture conditions for gene expression are cell density at the time of induction, shaking speed, induction temperature, induction time, and inducer concentration. The highest level for CAT1 was obtained at the IPTG concentration of 1.2 mM, 10 hours after induction at 35 °C, shaking speed 200 rpm with cell density at OD600 0.7.